2015
DOI: 10.1016/j.contraception.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy with use of progestin-only injectables and contraceptive implants: a systematic review

Abstract: Progestin-only contraceptive implants and injectables protect against ectopic pregnancy by being highly effective in preventing pregnancy overall; however, the absolute risk of ectopic pregnancy varies by type of progestin. Risk of ectopic pregnancy should not be a deterrent for use or provision of these methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 96 publications
(88 reference statements)
0
21
0
2
Order By: Relevance
“…Progestin-only contraceptive products, including LARC, have an established increased relative-risk for ectopic pregnancy, if fertilization does occur [12,13,29]. The pathophysiology is thought to be related to decreased smooth muscle contraction of fallopian tubes [13,29]. Fortunately, in our case the pregnancy was an ultrasound confirmed intra-uterine pregnancy, and Nexplanon was removed at 9 weeks gestation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Progestin-only contraceptive products, including LARC, have an established increased relative-risk for ectopic pregnancy, if fertilization does occur [12,13,29]. The pathophysiology is thought to be related to decreased smooth muscle contraction of fallopian tubes [13,29]. Fortunately, in our case the pregnancy was an ultrasound confirmed intra-uterine pregnancy, and Nexplanon was removed at 9 weeks gestation.…”
Section: Discussionmentioning
confidence: 87%
“…Serious complications such as ectopic pregnancy have been linked to contraceptive therapy. Progestin-only contraceptive products, including LARC, have an established increased relative-risk for ectopic pregnancy, if fertilization does occur [12,13,29]. The pathophysiology is thought to be related to decreased smooth muscle contraction of fallopian tubes [13,29].…”
Section: Discussionmentioning
confidence: 99%
“…Association between low progesterone level and EP have long been described, low serum progesterone influences the oviduct electrophysiological characteristics leading to poor ovum transfer, low probability of pro-uterine propagation of the activity at the fimbria end of the tube; high frequency but low number of electrical bursts, reflecting possible weak propulsive force and consequently increasing the rate of ovum retention and ectopic pregnancy (12,13) . The long term use of the progestin containing implant also causes myorelaxation and further increasing the rate of EP (4) . This together with multiparty are plausible mechanisms for the development of EP in our indexed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several original research and case reports have been published on the relationship between LNG as emergency contraception and ectopic pregnancy (EP) (1,5,6) . A recent systematic review in 2015 showed EP is more common if LNG containing implants is used compared to implants containing other hormones (4) . In this article the authors describes 2 cases of ectopic pregnancies diagnosed at 8 and 7 weeks of amenorrhea after the removal of levonorgestrel (LNG) -containing implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation